Film or Film Brand? UK Consumers' Engagement with Films as Brands. (4th April 2020) - Kohli, Gurdeep Singh; Yen, Dorothy; Alwi, Sharifah; Gupta, Suraksha
Abstract: Many films are produced annually, but only a small number of films reach the state of being considered and identified by consumers as film brands. Film‐brand identification is difficult to achieve, but it leads to engagement behaviours (e.g. repetitive viewing, positive word‐of‐mouth and purchase intention of relevant merchandise/franchise). To help film‐makers better develop films as brands and benefit from their brand status, this paper takes a consumer‐centric approach to investigate how and why films are identified and engaged by consumers as brands. Using an abductive mode of reasoning, a consumer film‐brand engagement framework was developed through qualitative data collected from 35 semi‐structured interviews and then validated using survey data with 1030 participants. This consumer film‐brand engagement framework shows that film identity coherency drives film‐brand identification through the mediation effects of popularity, sequels and emotional bonding, whilst marketing effort, iconic status, franchising/merchandising activities and timelessness are highlighted as key moderators, resulting in positive brand engagement behaviour. The paper sheds new light on film‐branding literature by theoretically explaining and empirically showing a sequential and consolidated process, which consumers go through to identify and engage with films as brands, leading to several managerial and marketing implications for film‐makers.